2016
DOI: 10.1007/s11881-016-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Teacher candidates’ mastery of phoneme-grapheme correspondence: massed versus distributed practice in teacher education

Kristin L. Sayeski,
Gentry A. Earle,
R. Paige Eslinger
et al.

Abstract: Matching phonemes (speech sounds) to graphemes (letters and letter combinations) is an important aspect of decoding (translating print to speech) and encoding (translating speech to print). Yet, many teacher candidates do not receive explicit training in phoneme-grapheme correspondence. Difficulty with accurate phoneme production and/or lack of understanding of sound-symbol correspondence can make it challenging for teachers to (a) identify student errors on common assessments and (b) serve as a model for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Similar to previous research on the effect of distributed practice on knowledge outcomes (Hocevar & Zimmer, 1994;Kupper-Tetzel, 2014;Sayeski et al, 2017), findings from this study demonstrated the efficacy of distributed practice on learning specific content (Research Question 1). Teacher candidates in the experimental condition significantly outperformed candidates in the business-as-usual condition.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to previous research on the effect of distributed practice on knowledge outcomes (Hocevar & Zimmer, 1994;Kupper-Tetzel, 2014;Sayeski et al, 2017), findings from this study demonstrated the efficacy of distributed practice on learning specific content (Research Question 1). Teacher candidates in the experimental condition significantly outperformed candidates in the business-as-usual condition.…”
Section: Discussionsupporting
confidence: 88%
“…Within higher education, several studies have demonstrated the power of distributed practice on students’ knowledge acquisition (Bude, Imbos, Van De Wiel, & Berger, 2011; Hocevar & Zimmer, 1994; Sayeski, Earle, Eslinger, & Whitenton, 2017). These studies have examined overall achievement in a college course (Hocevar & Zimmer, 1994) and on specific content-knowledge acquisition (Bude et al, 2011; Sayeski et al, 2017). Findings from the studies demonstrated greater gains in learning as a result of distributed practice.…”
Section: Applying Principles Of Learning Within Teacher Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors studied the effects of specific instruction on word-level knowledge and found that the experimental group showed a statistically significant level of improvement over the control group. Similarly, Sayeski, Earle, Eslinger, and Whitenton (2017) worked with 52 preservice teachers enrolled in special education methods courses to study how two different approaches to teaching phoneme–grapheme correspondence and phoneme production might affect knowledge growth. Within each of two courses, instructors either delivered phoneme–grapheme instruction in a “massed practice condition” (one session for 60 min) or a “distributed practice condition” (four 15-min sessions; p. 30).…”
Section: Resultsmentioning
confidence: 99%
“…; Fielding‐Barnsley, 2010). Sayeski, Earle, Eslinger, and Whitenton (2017) created an assessment that asked preservice teachers to orally provide the sounds associated with 56 letters or letter combinations (e.g., qu , oi ). Shaw et al (2007) created a short‐answer questionnaire that included three open‐ended questions that addressed technical knowledge (e.g., what are reading difficulties?)…”
mentioning
confidence: 99%